2013
DOI: 10.1038/srep02846
|View full text |Cite
|
Sign up to set email alerts
|

How ecological restoration alters ecosystem services: an analysis of carbon sequestration in China's Loess Plateau

Abstract: Restoring disturbed and over-exploited ecosystems is important to mitigate human pressures on natural ecosystems. China has launched an ambitious national ecosystem restoration program called Grain to Green Program (GTGP) over the last decade. By using remote sensing techniques and ecosystem modelling, we quantitatively evaluated the changes in ecosystem carbon sequestration since China's GTGP program during period of 2000–2008. It was found the NPP and NEP in this region had steadily increased after the initi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
235
0
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 368 publications
(252 citation statements)
references
References 20 publications
13
235
0
4
Order By: Relevance
“…The construction of sedimenttrapping dams and terraces will improve water-rich land and hence improve the ES of food production in the CM (Lü et al, 2012). Revegetation will not only reduce soil erosion from hill slopes (Feng et al, 2010), but will also enhance carbon sequestration (Feng et al, 2013). According to Lü et al (2012), water yield decreased across the entire Loess Plateau at an average rate of 10.3 mm year −1 during 2000-2008; however this was accompanied by a 3.4 billion tonne increase in annual average soil retention, 12.2 Tg increase in carbon sequestration and a 1.3 times increase in grain production.…”
Section: Altered Ecosystem Services In the Loess Plateaumentioning
confidence: 99%
“…The construction of sedimenttrapping dams and terraces will improve water-rich land and hence improve the ES of food production in the CM (Lü et al, 2012). Revegetation will not only reduce soil erosion from hill slopes (Feng et al, 2010), but will also enhance carbon sequestration (Feng et al, 2013). According to Lü et al (2012), water yield decreased across the entire Loess Plateau at an average rate of 10.3 mm year −1 during 2000-2008; however this was accompanied by a 3.4 billion tonne increase in annual average soil retention, 12.2 Tg increase in carbon sequestration and a 1.3 times increase in grain production.…”
Section: Altered Ecosystem Services In the Loess Plateaumentioning
confidence: 99%
“…An enrichment ratio of 1.1 was used to estimate the eroded OC from the topsoils. Furthermore, given that the sediments from gully erosion represent ∼ 50 % of the total (Xu, 1999;Zhao, 1996;Jing et al, 1998) and the lower SOC content of the subsoils relative to the topsoils (Wang et al, 2008;Feng et al, 2013), the enrichment ratio for half of the eroded soils from the subsoils was estimated at 0.8. The total eroded SOC was estimated at 1.07 ± 0.15 Gt during the period 1950-2010.…”
Section: Associated Organic Carbon Budgetmentioning
confidence: 99%
“…Feng et al (2013) investigated the Loess Plateau's ecosystem carbon storage dynamics and discovered its ecosystem had been a C source until 2000 when national vegetation restoration programs were launched. They found that the annual net ecosystem productivity was −0.011 Gt in 2000 and it had increased only in recent years.…”
Section: Implications Of Organic Carbon Emissionmentioning
confidence: 99%
“…In order to address the serious environmental and ecological issues, a series of large-scale ecological restoration projects were carried out throughout the world (Allana et al, 2013), and China has also taken efforts in such actions since the 1950s (Huang et al, 2009). Recently, two large-scale ecological restoration projects, i.e., the Natural Forest Conservation (NFC) project and the Grain for Green (GFG) project, have been launched to improve vegetation coverage in the Loess Plateau of North China (Feng et al, 2013;Liu et al, 2008). Undoubtedly, changes in vegetation directly or indirectly modify biosphere-atmosphere interactions, including the hydrological cycle and energy budgets Chapin et al, 2005).…”
Section: Introductionmentioning
confidence: 99%